2022
DOI: 10.1021/acs.jmedchem.1c01706
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Brain-Penetrant and Reversible Monoacylglycerol Lipase PET Tracers for Neuroimaging

Abstract: Monoacylglycerol lipase (MAGL) is one of the key enzymes in the endocannabinoid system. Inhibition of MAGL has been proposed as an attractive approach for the treatment of various diseases. In this study, we designed and successfully synthesized two series of piperazinyl pyrrolidin-2-one derivatives as novel reversible MAGL inhibitors. (R)-[18F]13 was identified through the preliminary evaluation of two carbon-11-labeled racemic structures [11C]11 and [11C]16. In dynamic positron-emission tomography (PET) scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…19 3-(2-Fluoro-6-methoxyphenethyl)azetidine 2,2,2-trifluoroacetate (9e) The procedure described for the synthesis of 4d was applied to 9d (110 mg, 0.36 mmol) and trifluoroacetic acid (0.30 mL, 4.27 mmol) to give a crude product, which was directly applied to the next step. LC-MS (ESI): (9). The procedure described for the synthesis of 4 was applied to 15 (28.0 mg, 0.09 mmol), 9e (30.0 mg, 0.09 mmol) and DIPEA (0.10 mL, 0.57 mmol) in MeCN (2 mL).…”
Section: Lc-ms (Esi)mentioning
confidence: 99%
See 2 more Smart Citations
“…19 3-(2-Fluoro-6-methoxyphenethyl)azetidine 2,2,2-trifluoroacetate (9e) The procedure described for the synthesis of 4d was applied to 9d (110 mg, 0.36 mmol) and trifluoroacetic acid (0.30 mL, 4.27 mmol) to give a crude product, which was directly applied to the next step. LC-MS (ESI): (9). The procedure described for the synthesis of 4 was applied to 15 (28.0 mg, 0.09 mmol), 9e (30.0 mg, 0.09 mmol) and DIPEA (0.10 mL, 0.57 mmol) in MeCN (2 mL).…”
Section: Lc-ms (Esi)mentioning
confidence: 99%
“…The IC 50 values of compounds were measured using MAGL enzyme as previously described [9]. The experiments were carried out at least in triplet using mouse or human MAGL.…”
Section: Magl Ic 50 Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F]MAGL-2102, [18 F]MAGL-1902, [ 18 F]YH149, [ 11 C]RO7279991, [ 11 C] PAD, and [18F]MAGL-4-11; Figure7) [119][120][121][122][123][124]. Scaffold selection from the compound libraries are often initially guided by potency measured by the half-maximal inhibitory concentration (IC 50 ), and followed by selectivity, reversibility, metabolic stability, or rate constant data.…”
mentioning
confidence: 99%
“…Fortunately, pre-treatment with the P-gp inhibitor elacridar enabled [ 11 C]SCIO-469 to pass the BBB with peak brain uptake of 1.2 SUV, indicating that the radiotracer is a substrate for rodent efflux transporters (Figure8(B)). A subsequent MDCK-MDR1 assay suggested that SCIO-469 is also likely to be a substrate F I G U R E 7 Structures of selected MAGL PET tracers [119][120][121][122][123][124]. Abbreviations: MAGL, monoacylglycerol lipase; PET, positron emission tomography.…”
mentioning
confidence: 99%